(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article explores the concept of patience (sabr) from both Islamic and psychological perspectives, highlighting its importance as a moral, spiritual, and psychological virtue. In Islamic teachings, patience is emphasized in the Qur’an and Hadiths as a key factor in personal development, social harmony, and spiritual growth. Prophets such as Ishmael, Idris, and Dhul-Kifl are presented as exemplars of patience, providing practical models for believers to follow. The study also integrates modern psychological insights, including stress management, coping strategies, delayed gratification, and emotional intelligence (Lazarus & Folkman, 1984; Frankl, 2006; Goleman, 1995). By combining religious-psychological analysis with contemporary research, the article shows that patience enhances mental resilience, emotional stability, goal achievement, and social adaptability. Finally, patience is highlighted as a mechanism for maintaining mental health, developing willpower, and fostering moral and spiritual growth. The study underscores that understanding and practicing patience can help individuals navigate life’s challenges while promoting psychological, social, and spiritual well-being.